Disturbing Flowers: The Three-Dimentional Colours of Claud. Rapt. Pros. 2.90-132 - Bersani, Beatrice (Classica et Mediaevalia, 2022)
Claudian’s colourful images have often been studied for their decorative func- tion and as examples of late-antique fragmentary style. More recent scholarship, instead, has proposed that colouring provides coherence to the text through its symbolic meanings. This article analyses the aesthetic and symbolic significance of colourful imagery by differentiating between the three main dimensions of colour: brightness, saturation and hue. The blossoming meadow of Claud. Rapt. Pros. 2.90-132 is an ideal case study: a focus on all three colour components highlights that the formal choices and the symbolic meanings are not opposite or separate, but parallel in their fragmentary coherence, and each important for the interpretation of the text. Both the visual effects and the metaphoric charge of Claudian’s colourful flowers undermine the idyllic atmosphere of the meadow and foreshadow Proserpina’s abduction.